Higher log position is not associated with better physical fitness in professional soccer teams in South Africa - Clark, JR (South African Journal of Sports Medicine, 2007)
Objective. To assess the difference in physical fitness of players in successful versus less-successful professional soccer teams in South Africa. Design. Professional soccer players (N = 140) underwent a battery of tests assessing important physiological components during the early part of their competitive season. Players were then separated into two groups on the basis of their teams’ final log position in the Premier Soccer League (PSL) in South Africa. Players in successful (N = 70) and less-successful (N = 70) teams were in the top four or bottom six positions on the log respectively. Descriptive statistics (mean ± standard deviation (SD)) were calculated for each group, and independent t-tests were used to compare the means of the groups for each of the physical tests. Main outcome measures. Body composition, flexibility, muscle strength-endurance, power, speed, agility, aerobic endurance, and repeat sprint distance. Results. There were no significant differences between groups for all measures of body composition, flexibility, repeat sprint distance, and agility. Significant differences (p < 0.05) were found for sit-ups, aerobic endurance, and speed, but these were generally small, not meaningful differences in performance. Players in successful squads were significantly (p < 0.01) older than those in less-successful teams. Conclusions. The results demonstrate that in South Africa level of physical fitness is not higher in more-successful compared with less-successful teams in the PSL. Factors other than physical fitness may be more important in determining successful league performance and discrimi-nate better between players in teams with different levels of success. Improving professional soccer performance may require coaches and trainers to focus more attention on technical and tactical skill development in sport-specific training once an acceptable standard of fitness has been attained.. South African Journal of Sports Medicine Vol. 19 (2) 2007: pp. 40-45